A preliminary DTI study showing no brain structural change associated with adolescent cannabis use - Brown Kyle; Majcher Magda; Szulc Kamila U; Bertisch Hilary C; DeLisi Lynn E; Bappal Arthika; Ardekani Babak A (BMC, 2006)
Abstract Analyses were performed on brain MRI scans from individuals who were frequent cannabis users (N = 10; 9 males, 1 female, mean age 21.1 ± 2.9, range: 18-27) in adolescence and similar age and sex matched young adults who never used cannabis (N = 10; 9 males, 1 female, mean age of 23.0 ± 4.4, range: 17-30). Cerebral atrophy and white matter integrity were determined using diffusion tensor imaging (DTI) to quantify the apparent diffusion coefficient (ADC) and the fractional anisotropy (FA). Whole brain volumes, lateral ventricular volumes, and gray matter volumes of the amygdala-hippocampal complex, superior temporal gyrus, and entire temporal lobes (excluding the amygdala-hippocampal complex) were also measured. While differences existed between groups, no pattern consistent with evidence of cerebral atrophy or loss of white matter integrity was detected. It is concluded that frequent cannabis use is unlikely to be neurotoxic to the normal developing adolescent brain.